2001
DOI: 10.4141/a00-022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-slaughter administration of oral calcium gel to beef cattle on tenderness

Abstract: . 2001. Effects of pre-slaughter administration of oral calcium gel to beef cattle on tenderness. Can. J. Anim. Sci. 81: 33-38. The effects of preharvest administration of oral calcium gel to beef cattle on longissimus pH, calpain activity, and tenderness were examined. Thirty steers (539 kg) were randomly assigned to one of the following treatments: control (CON, n = 15) and calcium gel administered (CA, n = 15). At 3 to 6 h prior to slaughter, the calcium gel steers were dosed via a rumen tube with calcium p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Increasing LM Ca through dietary means has (Goff and Horst 1993). In fact, orally administering Ca propionate 3 to 6 h before slaughter has been demonstrated to increase LM Ca and calpain activity, and improve tenderness in beef aged 4 and 7 d, when compared with LM from cattle not drenched with Ca propionate (Duckett et al, 2001). The fact that LM pH and Ca were not altered by DCAD in the present study suggests that the body is very good at maintaining homeostasis in regard to tissue pH and ion concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing LM Ca through dietary means has (Goff and Horst 1993). In fact, orally administering Ca propionate 3 to 6 h before slaughter has been demonstrated to increase LM Ca and calpain activity, and improve tenderness in beef aged 4 and 7 d, when compared with LM from cattle not drenched with Ca propionate (Duckett et al, 2001). The fact that LM pH and Ca were not altered by DCAD in the present study suggests that the body is very good at maintaining homeostasis in regard to tissue pH and ion concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Varner and Woods (1972) observed no differences in carcass characteristics when steers were fed diets containing 0.20, 0.31, 0.42, or 0.53% (diet DM) Ca. In addition, Duckett et al (2001) and Spears et al (2003) observed no differences in carcass traits when steers were administered Ca gel 3 to 6 h before slaughter or Ca propionate 7 d before slaughter, respectively. The lack of differences in carcass measurements may be attributed to adequate storage of Ca in bone of research 1 ZH (Merck Animal Health, Millsboro, DE) was supplemented at a rate of 8.33 mg/kg diet DM for 25 d followed by a 3-d withdrawal before harvest.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, percentage moisture lost as purge and during cooking was not affected by Ca depletion (P > 0.05). Duckett et al (2001) administered Ca gel to steers 3 to 6 h before slaughter and analyzed WBSF values at 2, 4, 7, 14, and 28 d postmortem. The authors observed lower WBSF values on d 4 and 7 of postmortem aging (P < 0.05), but in agreement with our results, no difference in WBSF values were detected at 14 d postmortem (P > 0.05) between steaks from treated and untreated cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Significant hypocalcemia was also reported by Shorthose and Shaw (1977) in slaughtered sheep. This might be due utilization of Ca ions by calpain proteolytic system (Duckett et al, 2001). Calcium is also utilized to maintain heart-beat and blood clotting mechanism (Kaneko et al, 2008).…”
Section: Resultsmentioning
confidence: 99%